Encontrabilidade da informação: contributo para uma conceituação no campo da Ciência da Informação - Vechiato, Fernando Luiz [UNESP] (2013)
Facing the evolution of information and communication technologies (ICT) and the infocommunicational actions carried out by the informational and institutional individuals in informational environments, we have the emergence of the findability as an important element which is situated between the information environments and systems, and informational individuals, which can be investigated in the field of Information Science through the perspective of mediation, since that it permeates the processes that make up the infocommunicational flow. Starting from this premise, we have evidenced the conceptual and practices contributions of findability for this scientific field by having the infocommunicational mediation as foundation. Facing as an hypothesis that the findability of information, allied to the concept of mediation, provides in practice the effectiveness of operation of the informational environments and information retrieval by informational individuals, we have conducted the investigation from the quadripolar method, which is based on the follow aspects: epistemological (epistemological pole), linked on the conception of an post-custodial paradigm which predominates the access to information, and the repositioning of ICT as one of the fields of Information Science; and theoretical (theoretical pole) which, through review of the literature (technical pole) allows us to understand the main theoretical approaches and operatives concepts that surround the object of this investigation. The research reached the following results (morphological pole): the inferences made in scientific text, the Attributes of the Findability of Information (AFI), the Model of the Findability of Information (MFI) and the Guidelines of the Findability of Information (GFI).